2020
DOI: 10.1155/2020/3501845
|View full text |Cite
|
Sign up to set email alerts
|

A New Measurement Based on HPB to Measure the Wall Pressure of Electric-Spark-Generated Bubble near the Hemispheric Boundary

Abstract: Direct measurement of the wall pressure loading of the spherical boundary subjected to the near-field underwater explosion is a great difficulty. To investigate the wall pressure caused by electric-spark-generated bubble near a hemispheric boundary, an experiment system is developed. In the method of this experiment, a Hopkinson bar (HPB), used as the sensing element, is inserted through the hole drilled on the hemisphere target and the bar’s measuring end face lies flush with the loaded face of the hemisphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Cui et al [ 25 ] used a high-voltage electric discharge to generate bubbles. Ma et al [ 19 ] improved upon the equipment of Cui et al by adding a replaceable target to realize bubble experiments under different curved surface boundaries. A voltage of 400 V discharged by the capacitor was transmitted to a thin copper tube through a wire, and bubbles were generated at the intersection of the two thin copper tubes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cui et al [ 25 ] used a high-voltage electric discharge to generate bubbles. Ma et al [ 19 ] improved upon the equipment of Cui et al by adding a replaceable target to realize bubble experiments under different curved surface boundaries. A voltage of 400 V discharged by the capacitor was transmitted to a thin copper tube through a wire, and bubbles were generated at the intersection of the two thin copper tubes.…”
Section: Methodsmentioning
confidence: 99%
“…This research showed that the established numerical method can accurately represent the morphological evolutionary characteristics of bubbles near the sphere boundary and also provided many detailed morphological characteristics. Ma Chunlong et al [ 19 ] gave the explosion distance parameter that affects the bubble load characteristics near the hemisphere boundary using the Hopkinson bar (HPB). However, few scholars have provided the load characteristics of bubbles near a curved surface boundary from an experimental research perspective, as most only provide some flow field characteristics in numerical terms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. GL. et al [7], Fong et al [8], Gong et al [9], Luo et al [10], Ma et al [11], Zhang et al [12], and Ma et al [13] used the same method. Klaseboer et al [14] used the same method.…”
Section: Introductionmentioning
confidence: 99%
“…Jayaprakash et al [25] used a pressure sensor to measure the wall pressure load generated by the spark bubble in the vertical direction. Cui et al [26], Yao et al [27,28], and Ma et al [13] used Hopkinson rods to measure spark bubble loads and micro-explosive bubble loads. Through previous research results, it is known that the explosion distance is an important cause of damage to surrounding structures due to the cavitation bubble load.…”
Section: Introductionmentioning
confidence: 99%